INFLUENCE OF DIETARY-PROTEIN INTAKE AND RECOMBINANT HUMAN SOMATOTROPIN ADMINISTRATION ON GROWTH AND BODY-COMPOSITION OF JUVENILE TAMBACU (A PIARACTUS-MESOPOTAMICUS X COLOSSOMA-MACROPOMUM CROSS) - Macari, Marcos [UNESP]; Carneiro, D. J.; Larson, M. L.; Machado, C. R. (Elsevier B.V., 1994)
This experiment was undertaken to study the interaction between level of dietary protein and recombinant human somatotropin (rhGH) administration on performance and body composition of juvenile tambacu (a crossbred Brazilian fish). A total of 72 juvenile tambacu, initially weighing and measuring (mean +/- s.e.m.) 23 +/- 2 g and 9 +/- 0.5 cm, respectively, were randomly divided into 18 groups of 4 fish each. Water temperature was 28 degrees C. Triplicate groups received one of two levels of dietary protein (15 and 30% as fed basis) and one of 3 doses of rhGH (0, 2 and 4 mu g/g) via intraperitoneal injection twice a week for 6 weeks, using a randomized complete block design. Somatotropin was noted to stimulate linear and body weight gain. The higher protein level supported increased growth in weight and length, but there was no interaction between protein level and rhGH dose for either parameter. Protein efficiency ratio and percentage protein deposited showed higher values on diets containing 15% protein. Somatotropin treatment did not significantly affect body composition, but there was a trend towards improved protein retention and reduced carcass lipid. In conclusion, the results of this experiment suggest that rhGH is able to stimulate linear gain in tambacu.
Keywords: (PIARACTUS MESOPOTAMICUS X COLOSSOMA MACROPOMUM); Somatotropin; SOMATOMEDIN; Tambacu; GROWTH, FISH; Growth hormone; PROTEIN INTAKE